(-5)3-(33+4).(-2)+(3-27):4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(27.65+27.35+300=27.\left(65+35\right)+300\)
\(=27.100+300=2700+300=3000\)
b)\(3838:\left[\left(190-6.5^2\right):4+3\right]\)
\(=3838:\left[\left(190-6.25\right):4+3\right]\)
\(=3838:\left[\left(190-150\right):4+3\right]\)
\(=3838:\left[40:4+3\right]=3838:\left[10+3\right]\)
\(=3838:13=\dfrac{3838}{13}\)
c)\(2022-x=2021\)
\(x=2022-2021=1\)
d)\(26+14:\left(x-5\right)=33\)
\(14:\left(x-5\right)=33-26=7\)
\(x-5=14+7=2\)
\(x=2+5=7\)
e)đề hỏi làm j thế bạn
1).( 27,56 x 35 ) + ( 27,56 x 67 ) - ( 27,56 x 2)
= (964 + 1846,52) - 55,12
=2810,52 - 55,12
= 2755,4
2).( 4x 35 ) x ( 25 x 5 ) x 2
= ( 140 x 125 ) x2
= 17500 x 2
=35000
4). 3/10
5). 1188
6). 61/6
1) \(3\sqrt{2}-4\sqrt{18}+2\sqrt{32}-\sqrt{50}\)
\(=3\sqrt{2}-12\sqrt{2}+8\sqrt{2}-5\sqrt{2}\)
\(=-6\sqrt{2}\)
2) \(\sqrt{50}-\sqrt{18}+\sqrt{200}-\sqrt{162}\)
\(=5\sqrt{2}-3\sqrt{2}+10\sqrt{2}-9\sqrt{2}\)
\(=3\sqrt{2}\)
3) \(5\sqrt{5}+\sqrt{20}-3\sqrt{45}\)
\(=5\sqrt{5}+2\sqrt{5}-9\sqrt{5}\)
\(=-2\sqrt{5}\)
4) \(5\sqrt{48}-4\sqrt{27}-2\sqrt{75}+\sqrt{108}\)
\(=20\sqrt{3}-12\sqrt{3}-10\sqrt{3}+6\sqrt{3}\)
\(=4\sqrt{3}\)
5) \(\dfrac{1}{2}\sqrt{48}-2\sqrt{75}-\dfrac{\sqrt{33}}{\sqrt{11}}+5\sqrt{1\dfrac{1}{3}}\)
\(=2\sqrt{3}-10\sqrt{3}-\sqrt{3}+\dfrac{10}{3}\sqrt{3}\)
\(=-\dfrac{17}{3}\sqrt{3}\)
a) \(3x-13=2\)
\(\Rightarrow3x=2+13\)
\(\Rightarrow3x=15\)
\(\Rightarrow x=15:3\)
\(\Rightarrow x=5\)
Vậy \(x=5\)
b) \(27-\left(5x+4\right)=13\)
\(\Rightarrow5x+4=27-13\)
\(\Rightarrow5x+4=14\)
\(\Rightarrow5x=14-4\)
\(\Rightarrow5x=10\)
\(\Rightarrow x=10:5\)
\(\Rightarrow x=2\)
Vậy \(x=2\)
c) \(2.5^x-33=2^3+3^2\)
\(\Rightarrow2.5^x-33=8+9\)
\(\Rightarrow2.5^x-33=17\)
\(\Rightarrow2.5^x=17+33\)
\(\Rightarrow2.5^x=50\)
\(\Rightarrow5^x=50:2\)
\(\Rightarrow5^x=25\)
\(\Rightarrow5^x=5^2\)
\(\Rightarrow x=2\)
Vậy \(x=2\)
\(\frac{\left(\frac{518}{19}-\frac{342}{13}\right).\left(\frac{177}{236}+\frac{76}{236}-\frac{6}{236}\right)}{\left(\frac{3}{4}+x\right).\frac{27}{33}}=1\)
=>\(\frac{\left(\frac{6734}{247}-\frac{6498}{247}\right).\frac{247}{236}}{\left(\frac{3}{4}+x\right).\frac{27}{33}}=1\)
=>(3/4+x)*27/33=236/247*247/236=1
3/4+x=1:27/33=33/27
x=33/27-3/4=132/108-81/108
x=51/108
Vậy x=51/108
11: Ta có: \(\left(x+3\right)^3=125\)
\(\Leftrightarrow x+3=5\)
hay x=2
12: Ta có: \(\left(2x\right)^4=16\)
\(\Leftrightarrow x^4=1\)
hay \(x\in\left\{1;-1\right\}\)
=-225+62-6=-169
\(\left(-5\right)^3-\left(3^3+4\right).\left(-2\right)+\left(3-27\right):4\)
\(=-125-\left(31\right).\left(-2\right)+\frac{-24}{4}\)
\(=-125+62-6\)
\(=-69\)